THE IMPLEMENTATION OF SOCIO-AFFECTIVE STRATEGIES IN IMPROVING INDONESIAN JUNIOR SECONDARY SCHOOL STUDENTS’ SPEAKING ABILITY - Nurwandi Nurwandi; Chairil Anwar Korompot; Sultan Baa (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
The study aimed at finding out: (1) whether the implementation of socio-affective strategies could improve Indonesian junior secondary school students’ English speaking ability; and (2) the students’ perceptions on the implementation of socio-affective strategies in teaching and learning English speaking skill. The study employed quantitative research method. Pre-experimental research design was used to assess the improvement of the students’ English speaking ability and questionnaire was used to find out the students’ perception on socio-affective strategies in English speaking classroom. Thirty three (33) seven grade students of Public Islamic Junior Secondary School (MTs. Negeri) Gowa Regency South Sulawesi Province were taken as samples of the study by using cluster random sampling technique. The pre-test and post-test results were collected from the students’ speaking assessment then analyzed by using IBM Statistic SPSS 20 Software. Questionnaire responses were classified into sub-themes and then analyzed using percentage. The study found: (1) the t-test value of English speaking ability was greater than t-table (16.476>1.693). Therefore, the alternative hypothesis (H1) was accepted and null hypothesis (H0) was rejected. It can be concluded that there was significant improvement on students’ English speaking ability by implementing socio-affective strategies at the seventh grade students of MTs Negeri Gowa Regency; (2) the result of questionnaire analysis showed that the students had positive responses to the implementation of socio-affective strategies in speaking class with the range score of 130-142. In addition, the students believed that socio-affective strategies have benefit to their interest and behavior toward language learning, and improved their English speaking ability.